The Effectiveness of Video-Based POE2WE Model on Magnetic Induction Materials in the COVID 19 Pandemic - Fifi Aprilia; Nana Nana; Dwi Sulistyaningsih (Jurnal Pembelajaran Fisika, 2020)
This study aims to determine the effectiveness of the POE2WE model in learning, determine the effectiveness of using video in learning, determine the effectiveness of the video-based POE2WE model in learning, and determine the level of understanding of the research object. The research method used is a quantitative method in the form of a survey. The quantitative method is a scientific research method whose data is in the form of numbers or statistics. Meanwhile, the survey is a technique of collecting data about a population using a sample. The objects in the study were 57 students of the Siliwangi University Physics Education class of 2018. The results of the study showed that the video-based learning model on magnetic induction material was effective in the pandemic.Keywords: POE2WE model, learning videos, and pandemic periodDOI: http://dx.doi.org/10.23960/jpf.v8.n2.202007